PRONUNCIATION ERROR PERFORMANCE OF ENGLISH DEPARTMENT STUDENTS OF MUHAMMADIYAH UNIVERSITY OF MALANG - Ega Septiani; Nina Inayati (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2015)
Pronunciation is the way in which a language or a particular word or sound is spoken. The aim of this research is to know the segmental phonemes errors made by the students at first-semester of English Department, University of Muhammadiyah Malang in learning English pronunciation.The research design used in this research is descriptive quantitative research design. Based on the result of this research there are 59 or 47% errors of pronunciation in vowel sound which was made by 20 students, 25 or 20% errors of pronunciation in consonants sound which was made by 14 students, and also 42 or 33% errors of pronunciation in diphthongs which were made by 19 students. Also, the most dominant errors made by the students were errors in pronouncing vowel sounds.